(untitled) (International Journal of Innovative Technologies in Economy, 2025)
The goal of this research is to investigate how transformational leadership, organizational culture, and Organizational Citizenship Behavior (OCB) impact the performance of teachers in Kanisius Catholic Elementary Schools in Yogyakarta City, Indonesia. The research adopts an ex-post facto design with a quantitative approach. The study population consisted of 75 teachers from seven Kanisius Catholic Elementary Schools in Yogyakarta. Information was gathered through questionnaires and examined utilizing SPSS 27, incorporating basic and multiple linear regression techniques. The findings indicate that: (1) Transformational leadership has a significant positive effect on teacher performance (t = 4.052, p < 0.05); (2) Organizational culture shows a positive influence in simple regression analysis (p = 0.001) but becomes non-significant in multiple regression (t = -1.310); (3) OCB has a significant positive impact on teacher performance (t = 9.184, p < 0.05); (4) Collectively, the three independent variables significantly affect teacher performance (F = 92.878, p < 0.05), with a coefficient of determination (R²) of 0.788. These findings indicate that teacher performance is influenced by transformational leadership, organizational culture, and OCB.